(untitled) (Nigerian Journal of Technology, 2016)
Renewable energy sources have gained much attention due to the recent energy crisis and the urge to get clean energy. Among the main options being studied, wind energy is a strong contender because of its reliability due to the maturity of the technology, good infrastructure and relative cost competitiveness. It is also interesting to note that there are physical limits to the potential height of a wind turbine tower since the mechanical structure of wind turbines are thus very flexible and tend to oscillate. This makes the design of wind turbines a demanding task. In this paper, the oscillation of a wind turbine tower due to imbalance in the masses of the blades is modeled in maplesim and the effect of the tower height on its oscillation was simulated. For a wind turbine with three rotor blades, two of which have masses of 10 kg, a mass moment of inertia of approximately 20 kg/m2 and one of the blades has a moment of inertia which is 1% less than the other blades. The simulation showed the most stable system for the most energy capture for this case study to be a rotor speed of 5.5rad/s at a height of 10m. At this angular frequency the deflection of the top of the wind turbine was approximately 1mm. http://dx.doi.org/10.4314/njt.v36i1.16